Bipolar Disorder and Polysubstance Use Disorder: Sociodemographic and Clinical Correlates - Aguglia, Andrea; Natale, Antimo; Fusar-Poli, Laura; Amerio, Andrea; Bruno, Edoardo; Placenti, Valeria; Vai, Eleonora; Costanza, Alessandra; Serafini, Gianluca; Aguglia, Eugenio; Amore, Mario (Frontiers in Psychiatry, 2022)
Introduction: Patients with bipolar disorder (BD) often show comorbidity with substance use disorder (SUD) with negative impact on clinical course, prognosis, and functioning. The role of polysubstance use disorder (polySUD) is understudied. The aim of the present paper is to evaluate the sociodemographic and clinical characteristics associated with BD and comorbid SUD, focusing on polySUD, in order to phenotype this specific group of patients and implement adequate treatment and prevention strategies. Methods: A cross-sectional study was conducted involving 556 patients with a primary diagnosis of BD (376 without SUD, 101 with SUD and 79 with polySUD). A semi-structured interview was administered to collect sociodemographic variables, clinical characteristics and pharmacological treatment. ANOVA and chi-square tests were used to compare the three groups. Significantly different variables were then inserted in a multivariate logistic regression. Results: Patients affected by BD and polySUD were younger and more frequently males and single than patients with SUD or without SUD. Indeed, the prevalence of patients affected by BD and polySUD living in public residences was higher than the other groups. Moreover, earlier age at onset, higher prevalence of psychotic and residual symptoms, involuntary hospitalization, and a family history of psychiatric disorders were associated with polySUD in patients suffering from BD. Lastly, patients with BD and polySUD were more likely to take four or more medications, particularly benzodiazepines and other drugs. At the multinomial regression, younger age, male gender, early age at onset, psychotic and residual symptoms, positive family history for psychiatric disorders, and use of benzodiazepines remained significantly associated with polySUD in patients with BD. Conclusions: Our findings show a specific profile of patients with BD and polySUD. It is important to focus research on this topic, in order to adopt specific therapeutic strategies, minimize the use of polypharmacy and aim at full remission and mood stabilization.